2013
DOI: 10.6090/jarq.47.103
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of B Cell Lymphomas in Cattle Infected with Bovine Leukosis Virus

Abstract: Lymphoid neoplasms in 17 cattle having tested positive for bovine leukosis virus (BLV) were investigated by histology and immunohistochemistry. In 16 cases, the neoplastic cells were characterized by a marked variation in cell size, atypia in large cells, nuclear irregularity in smaller cells, and nucleolar prominence in cells with scant cytoplasm. These cytological features were used to specifically define pleomorphic lymphomas. In addition to lymphoid cells, immunoblastoid and plasmacytoid cells containing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…Mitotic figures were present. Iwama et al [21] and Branco et al [22] observed similar histological features.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Mitotic figures were present. Iwama et al [21] and Branco et al [22] observed similar histological features.…”
Section: Discussionsupporting
confidence: 59%
“…Grossly, the enlargement was noticed in prescapular and precrural lymph nodes in calves and there was enlargement and fusion of mesenteric lymph nodes in the cow. The affected organs were soft, fleshy, greyish white and on cut section, the lymph nodes showed bulging and a homogenous pale appearance with no demarcation between cortex and medulla [14,15,[19][20][21]. Impression smears collected from affected lymph nodes and organs like heart, lung, liver and kidney revealed numerous cells which included lymphocytes, prolymphocytes and lymphoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Large and pleomorphic cells including cells with prominent nucleoli are observed in the pleomorphic variant of human mantle cell lymphoma (Swerdlow et al 2008). In contrast, the current cases showed histological transition from neoplastic mantle cells to larger and more pleomorphic cells, and the latter morphologically corresponded to pleomorphic B cell lymphoma cells (Murayama et al 2011, Iwama et al 2013, Hagiwara et al 2014. Lymph nodes composed chiefly of neoplastic pleomorphic cells showed a tendency toward severe enlargement in case 1, and thus were considered to be in the later stages of tumor development.…”
Section: Discussionmentioning
confidence: 53%
“…The absence of cIg in human and bovine mantle cell lymphomas can be explained by the fact that mantle cells correspond to naive pre-germinal center B cells (Feller & Diebold 2004). Pleomorphic B cell lymphoma is characterized by a lack of staining for cIg in cattle (Iwama et al 2013); therefore, we suggest that neoplastic mantle cells in the present cases have transformed into more atypical and pleomorphic cells, but have not differentiated into more mature cells such as cIg-producing immunoblasts (Murayama et al 2011).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation